Routes to a Green Transport Corridor Øresund-Hamburg - Hansen, Leif Gjesing; Serin, Göran; Lohse, Sandrina (Proceedings from the Annual Transport Conference at Aalborg University, 2013)
Routes to a green transport corridor Öresund – Hamburg Leif Gjesing Hansen, Senior Adviser and project manager, Region Zealand.